التناص في شعر سراقة البارقي "ت. 79 هـ. - 698 م." - السعوي، كوثر بنت عبدالله (جامعة القلم للعلوم الإنسانية والتطبيقية, 2022)
لسراقة البارقي وشعره مكانة في تراثنا العربي، بما تميز به من خصائص فنية وموضوعية، وجاءت هذه الدراسة لتسلط الضوء على ظاهرة أسلوبية، وخاصية من خصائصها، عن التناص في شعره، فكان هذا البحث للوقوف مع خصائص التناص في شعره، وبيان أنواعه، فحصرت شواهده، وبينت خصائصه. ثم كانت خاتمة البحث ذكرت فيها أبرز نتائج الدراسة والتوصيات، وكان من نتائج الدراسة ما يأتي: 1. كثرة تناص سراقة البارقي مع القرآن الكريم، ولا غرو في هذا فالنص القرآني بقصصه ومعانيه ولغته يعد أكثر المصادر توظيفا، وأوسعها تأثيرا في المضامين الشعرية قديما وحديثا. 2. كثرة تناص سراقة مع الشعر ‏بعامة، والشعر ‏الجاهلي على وجه الخصوص، وظهر ذلك في كثير من الأغراض والمعاني، تجلى ذلك في تقارب في الألفاظ، والتقاء في التراكيب، وتشابه في الصور. 3.‏ قلة تناص سراقة مع شعراء عصره، ربما كان ذلك بسبب تأثره بشعراء العصر الجاهلي، وبما وصل إليه من نضج فني، فكان الشعر الجاهلي المثل الأعلى الذي يسير الشعراء على منواله، ويقتفون أثره. 4. للنثر نصيب من التناص في شعر سراقة، وإن كان ذلك قليلا بمقارنته بالشعر، ومع ذلك فيظل النثر بأمثاله وحكمه حاضرا في شعر سراقة، ولذا تعددت شواهده، فقد اتخذ سراقة من الأمثال مصدرا لصوره، فقد أمدته ببعض الصور الحكيمة وذكرها في شعره. This article aims to shed light on the intertextuality in Suraqa Albarqi’s poetry. Albarqi and his poetry have a place in our Arab heritage, with its artistic and objective characteristics. It also aims to shed light on a stylistic phenomenon, i.e. the intertextuality in Albaqri’s poetry and its characteristics. The researcher discusses this phenomenon, its characteristics, its types, evidence, etc. The study concludes with some findings, the most important of which are: 1. It is not surprising to see the intertextuality in Suraqa Albarqi’s poetry with the Holy Qur’an, as the Qur’anic text with its stories, meanings and language is after the most widely used sources, and the most influential in poetic contents, ancient and modern. 2. It is also not surprising to find Albaqri’s poetry intertextualized with poetry in general, and pre-Islamic poetry in particular, which occurred for many purposes and meanings. This was manifested in closeness in words, convergence in structures, and similarity in figures. 3. The lack of intertextuality with the poets of his time; perhaps this was because he was influenced by the poets of the pre- Islamic era, and due to the artistic maturity, that he reached. Pre-Islamic poetry was the ideal that poets follow and imitate. 4. Prose has also some sort intertextuality in Suraqa’s poetry, though not much compared to poetry. Nevertheless, the prose of his parables and his wisdom remains present in his poetry. Therefore, his evidence was numerous. Albarqi took proverbs as a source for his figures. They provided him with some wise images and he mentioned them in his poetry.
Keywords: النقد الأدبي -- الشعر العربي -- التناص اللغوي -- التراث العربي -- البارقي، سراقة بن مرداس، ت. 79 هـ